VERIFIKASI KUALITAS ANALISIS MANGAN MENGGUNAKAN TEKNIK ICP-OES DALAM SAMPEL AIR MINUM - Risma Sari; Sutopo, Fiotentinada Puspita (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2024)
Drinking water quality, including the levels of dissolved metals, is an important public health consideration. Manganese (Mn) is a naturally occurring metal that can be present in drinking water sources, and excessive intake of Mn can have adverse health effects. The objective of this study was to verify the performance of the analytical method for the determination of manganese (Mn) concentration in drinking water samples using Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES) techniques at the PT XYZ Laboratory. The method verification included tests for analyte identity confirmation, linearity, precision, accuracy, as well as the determination of the Method Detection Limit (MDL) and Limit of Quantification (LOQ). The verification results showed that the ICP-OES method met the established performance requirements. The linearity test yielded a correlation coefficient (r) of 0.9998, fulfilling the criteria of r ≥ 0.995. The percent relative standard deviation (% RSD) value in the precision test was 1.41%, meeting the requirement of % RSD ≤ 2/3 % CV Horwitz. The accuracy test provided an average percent recovery of 98.66%, which is within the acceptable range of 85-120%. The determined MDL was 0.0006 mg/L, while the LOQ was 0.002 mg/L, both meeting the criteria of MDL < spiked concentration < 10 MDL and LOQ < environmental quality standard. In conclusion, the method for the determination of Mn concentration in drinking water using ICP-OES has been verified and can be used for routine analysis at the PT. XYZ Laboratory, supporting the monitoring and control of Mn levels in drinking water to ensure public health protection.